Catalytic Polysulfide Conversion and Physiochemical Confinement for Lithium–Sulfur Batteries. Issue 22 (27th April 2020) - Sun, Zixu; Vijay, Sudarshan; Heenen, Hendrik H.; Eng, Alex Yong Sheng; Tu, Wenguang; Zhao, Yunxing; Koh, See Wee; Gao, Pingqi; Seh, Zhi Wei; Chan, Karen; Li, Hong
Abstract: The lithium–sulfur (Li–S) battery is widely regarded as a promising energy storage device due to its low price and the high earth‐abundance of the materials employed. However, the shuttle effect of lithium polysulfides (LiPSs) and sluggish redox conversion result in inefficient sulfur utilization, low power density, and rapid electrode deterioration. Herein, these challenges are addressed with two strategies 1) increasing LiPS conversion kinetics through catalysis, and 2) alleviating the shuttle effect by enhanced trapping and adsorption of LiPSs. These improvements are achieved by constructing double‐shelled hollow nanocages decorated with a cobalt nitride catalyst. The N‐doped hollow inner carbon shell not only serves as a physiochemical absorber for LiPSs, but also improves the electrical conductivity of the electrode; significantly suppressing shuttle effect. Cobalt nitride (Co4 N) nanoparticles, embedded in nitrogen‐doped carbon in the outer shell, catalyze the conversion of LiPSs, leading to decreased polarization and fast kinetics during cycling. Theoretical study of the Li intercalation energetics confirms the improved catalytic activity of the Co4 N compared to metallic Co catalyst. Altogether, the electrode shows large reversible capacity (1242 mAh g −1 at 0.1 C), robust stability (capacity retention of 658 mAh g −1 at 5 C after 400 cycles), and superior cycling stability at high sulfur loading (4.5 mg cm −2 ). Abstract : A double‐shelled hollow nanocage decorated with cobalt nitride embedded in nitrogen‐doped carbon is employed as the cathode for lithium sulfur batteries. Cobalt nitride efficiently catalyzes polysulfide conversion. The porous and hollow structure facilitates physiochemical polysulfide adsorption, and effectively accommodates volume expansion. As a result, the shuttle of polysulfide in lithium sulfur batteries is greatly suppressed.